Tortricidae from Ethiopia, 3 (Insecta: Lepidoptera) - J. Razowski; P. Trematerra; M. Colacci (SHILAP)
Twenty-two species are discussed, and five species are described as new (Parabactra addisalema Razowski & Trematerra, sp. n., Megaherpystis subae Razowski & Trematerra, sp. n., Megaherpystis oromiae Razowski & Trematerra, sp. n., Eucosmocydia zegieana Razowski & Trematerra, sp. n., Thaumatographa amarana Razowski & Trematerra, sp. n.). New combinations: Polychrosis acanthis Meyrick, 1920 is transferred to Emrahia Koçak, 1981, Eucosma accipitrina Meyrick, 1913, Eucosma calliarma Meyrick, 1909, Eucosma nereidopa Meyrick, 1927, Cosmetra maficana Razowski, 2015, Cosmetra podocarpivora Razowski & Brown, 2012, and Cosmetra taitana Razowski & Brown, 2015, to Megaherpystis Diakonoff, 1969. Known species of Megaherpystis are listed. Females of Endothenia ethiopica Razowski & Trematerra, 2010, and Gypsonoma giorgiae Razowski & Trematerra, 2012 are newly described